MENGAFIRMASI INERANSI ALKITAB SEBAGAI SUMBER OTORITAS PENGAJARAN - Rudy Budiatmaja (Bethel Press, 2022)
The authenticity of the Bible has been a topic of discussion for a long time. Those communities reject the authenticity of the Bible. The problem is that the authorship and content of the Bible cannot be defended. These people echo their teachings through YouTube shows, publishing books, and journals. Anti-Biblical groups from all walks of life will continue to echo doubts about the Bible's authenticity. This study aims to affirm the inerrancy of the Bible as a valid truth in the Christian faith. This study uses a qualitative literature study approach that discusses etymology, understanding, theories, and concepts of expert opinion used to analyze the Bible. The results of the study stated that the truth of God's Word in the Bible was genuinely actual without the slightest error in both inerrancy and infallibility.